Israeli Territorial Annexation in Occupied Palestinian Territory: The Ambivalence of International Law - Aasi, Joni (Universitas Airlangga, 2022)
The enactment of Israeli policy on the occupied Palestinian territory has shown the development of the annexation of Israel”from the